Cell Specific Cytotoxicity and Uptake of Graphene Nanoribbons - Chowdhury, Sayan Mullick (2012)
The synthesis of oxidized graphene nanoribbons (O-GNR) via longitudinal unzipping of carbon nanotubes opens avenues for their further development for a variety of biomedical applications. Evaluation of the cyto- and bio-compatibility is necessary to develop any new material for in vivo biomedical applications. In this study, we report the cytotoxicity screening of O-GNRs water-solubilized with PEG-DSPE (1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[amino(polyethylene glycol)]), using six different assays, in four representative cell lines; Henrietta Lacks cells (HeLa) derived from cervical cancer tissue, National Institute of Health 3T3 mouse fibroblast cells (NIH-3T3), Sloan Kettering breast cancer cells (SKBR3) and Michigan cancer foundation-7 breast cancer cells (MCF7). These cell lines significantly differed in their response to O-GNR-PEG-DSPE formulations; assessed and evaluated using various endpoints (lactate dehydrogenase (LDH) release, cellular metabolism, lysosomal integrity and cell proliferation) for cytotoxicity. In general, all the cells showed a dose-dependent (10–400 μg/ml) and time-dependent (12–48 h) decrease in cell viability. However, the degree of cytotoxicity was significantly lower in MCF7 or SKBR3 cells compared to HeLa cells. These cells were 100% viable upto 48 hours, when incubated at 10μg/ml O-GNR-PEG-DSPE concentration, and showed decrease in cell viability above this concentration with ~78% of cells viable at the highest concentration (400 μg/ml). In contrast, significant cell death (5–25% cell death depending on the time point, and the assay) was observed for HeLa cells even at a low concentration of 10μg/ml. The decrease in cell viability was steep with increase in concentration with the CD(50) values ≥ 100μg/ml depending on the assay, and time point. Transmission electron microscopy of the various cells treated with the O-GNR solutions show higher uptake of the O-GNR-PEG-DSPEs into HeLa cells compared to other cell types. Additional analysis indicates that this increased uptake is the dominant cause of the significantly higher toxicity exhibited by HeLa cells. The results suggest that water-solubilized O-GNR-PEG-DSPEs have a heterogeneous cell-specific cytotoxicity, and have significantly different cytotoxicity profile compared to graphene nanoparticles prepared by the modified Hummer’s method (graphene nanoparticles prepared by oxidation of graphite, and its mechanical exfoliation) or its variations.